Guía para la Utilización Exitosa del Compost en la Producción de Hortalizas - Mónica Ozores-Hampton; Brain Asmad (EDIS)
HS1161, a 7-page Spanish-language fact sheet by Mónica Ozores-Hampton and Brain Asmad, provides a guide to the successful use of compost to produce vegetables. Published by the UF Department of Horticultural Sciences, March 2010.